Intravascular brachytherapy is a good clinical option for refractory in‐stent restenosis. Issue 1 (18th January 2021) - Balter, Stephen; Moses, Jeffrey W.
Key Points: VBT is a good clinical option for patients with refractory recurrent ISR in the DES era. IVUS guidance improves vessel characterization, with consequential improvements in treatment planning and delivery, significantly improves outcomes. Overall, VBT had a 2 year success rate of approximately 67% in 143 lesions. Optimizing treatment planning and delivery should further increases success.